2018
DOI: 10.1111/ajt.14584
|View full text |Cite|
|
Sign up to set email alerts
|

Antibody-mediated rejection: New approaches in prevention and management

Abstract: Estimated Time to Complete this Activity: 1.25 hours OverviewThis article reviews the pathophysiology of antibody-mediated rejection (AMR) with emphasis on the role of complement in allograft injury. It reviews the required features for a definitive diagnosis of AMR according to the latest Banff criteria, which incorporate recent findings delineating the complex spectrum of AMR and the diverse phenotypes seen. Clinical data on current and investigational treatments are summarized, and strategies to improve out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
109
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(110 citation statements)
references
References 100 publications
(70 reference statements)
0
109
1
Order By: Relevance
“…Hence, PIs now provide the foundation as a therapeutic strategy to safely and effectively treat a number of PCrelated human diseases. [8][9][10] HLA Abs, which arise from pregnancy, blood transfusion, or prior transplantation, present a significant and often impenetrable barrier to kidney transplantation, leading to increased morbidity and mortality. [5][6][7] It is now clear in kidney transplantation that Ab-mediated rejection (AMR) is the major cause of renal allograft loss, and HLA Abs also promote AMR in heart, lung, and pancreas transplantation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, PIs now provide the foundation as a therapeutic strategy to safely and effectively treat a number of PCrelated human diseases. [8][9][10] HLA Abs, which arise from pregnancy, blood transfusion, or prior transplantation, present a significant and often impenetrable barrier to kidney transplantation, leading to increased morbidity and mortality. [5][6][7] It is now clear in kidney transplantation that Ab-mediated rejection (AMR) is the major cause of renal allograft loss, and HLA Abs also promote AMR in heart, lung, and pancreas transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] It is now clear in kidney transplantation that Ab-mediated rejection (AMR) is the major cause of renal allograft loss, and HLA Abs also promote AMR in heart, lung, and pancreas transplantation. [8][9][10] HLA Abs, which arise from pregnancy, blood transfusion, or prior transplantation, present a significant and often impenetrable barrier to kidney transplantation, leading to increased morbidity and mortality. 11,12 Current desensitization therapies do not impact Ab production or eliminate bone marrow plasma cells (BMPCs).…”
Section: Introductionmentioning
confidence: 99%
“…Because there is no standardized treatment for ABMR, clinical application of ABMR treatment greatly varies between centers while effectiveness of currently available treatment options is limited . With some novel treatments directly affecting the complement system, the complement‐fixing ability of DSA may guide the choice of treatment as well as how to monitor for treatment success.…”
Section: Clinical Relevance Of Modified Luminex Sab Assaysmentioning
confidence: 99%
“…This complex is the most polymorphic gene system in human genome encoding more than 17 000 allelic variants . The characterization and matching of HLA alleles between donor and recipient is important for the successful outcome of hematopoietic stem cell and solid organ transplantation …”
Section: Conflict Of Interestmentioning
confidence: 99%
“…2 The characterization and matching of HLA alleles between donor and recipient is important for the successful outcome of hematopoietic stem cell and solid organ transplantation. [3][4][5] During the study of HLA typing of a related potential donor for stem cell transplantation, we found a sequence largely homologous to B*14:02:01 with a substitution at position 506 a C instead a G. This substitution results in a coding change from Arginine to Proline in exon 3 (codon 145b CGC ! CCC) ( Figure 1).…”
mentioning
confidence: 98%